The Molecular Genetics of Lung Cancer - Cooper, David N. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Lung cancer is the leading cause of cancer mortality in Western countries. It also provides an archetypal example of how inherited predisposing genetic variants may interact with an environmental influence (smoking) to modulate individual cancer risk. The Molecular Genetics of Lung Cancer describes how the new techniques, methods and approaches of molecular genetics are being used to unravel the complexities of the mechanisms underlying lung tumorigenesis by analysis at the DNA, RNA and protein levels with potentially important implications for tumour classification, diagnosis, prognosis and treatment as well as providing new insights into how lung tumours arise and how they progress to malignancy.